2021
DOI: 10.25259/sni_44_2021
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-induced encephalopathy and permanent neurological deficit: A case report and literature review

Abstract: Background: Contrast-induced encephalopathy (CIE) is a rare condition that occurs after intravenous or intra-arterial contrast agent administration. Patients generally show different ranges of neurological deficits, which generally resolve themselves spontaneously within 24–48 h or in rare cases within 2 weeks. Case Description: We report a case of CIE in a 54-year-old woman during retreatment for recanalization of communicating anterior artery aneurysm and with no history of allergic reaction to contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 8 publications
2
20
0
Order By: Relevance
“…Transient cortical blindness is the most common manifestation [10]. The literature review indicated that symptoms of neurological dysfunction presented within minutes to hours after contrast agent administration, and most patients fully recovered within 48-72 hours with supportive management [7][8][9]. In our patient, the symptoms resolved completely within 48 hours, which was consistent with the clinical course of CIE. We suspect that the severity of symptoms in our patient was related to her advanced age, hypertension, and other risk factors, which may have increased blood-brain barrier permeability, resulting in neurotoxicity and CIE.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Transient cortical blindness is the most common manifestation [10]. The literature review indicated that symptoms of neurological dysfunction presented within minutes to hours after contrast agent administration, and most patients fully recovered within 48-72 hours with supportive management [7][8][9]. In our patient, the symptoms resolved completely within 48 hours, which was consistent with the clinical course of CIE. We suspect that the severity of symptoms in our patient was related to her advanced age, hypertension, and other risk factors, which may have increased blood-brain barrier permeability, resulting in neurotoxicity and CIE.…”
Section: Discussionsupporting
confidence: 82%
“…This supports the hypothesis that the symptoms are a result of the chemotoxic effect of hyperosmolar media resulting in microvascular sludging and arterial spasms, causing shrinkage of the endothelial cells and disruption of tight junctions. The accumulation of iodinated contrast has also been known to cause a localized neurotoxic effect on the blood-brain barrier by increasing the expression of endothelin, amplifying endothelial cell permeability, and resulting in cerebral edema [7][8][9]. However, in our case, the contrast was administered intravenously for a CTPE study.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…4 Although mostly transient and reversible, the symptoms may be persistent with permanent sequelae and adverse clini-cal outcomes. 5 Herein, we report a case of CIE following flow diverter treatment that mimicked a severe anterior circulation stroke.…”
Section: Introductionmentioning
confidence: 97%